Low-profile balloon gastrostomy – prospective evaluation - Biernacki, Filip; Majewska, Krystyna; Sobocki, Jacek (Nursing in the 21st Century, 2025)
Aim. The aim of this study was to evaluate selected parameters of the nutritional treatment process in Home Enteral Nutrition (HEN) patients with a low-profile balloon gastrostomy. Material and methods. Fourteen HEN patients who had a low-profile balloon gastrostomy in December 2024 were included in the study. Patient data were collected from medical records from the HEN procedure qualification and during follow-up visits. Results. The majority of patients had normal biochemical parameters for nutritional status at baseline and during follow-up, while their BMI was below normal. None of the patients had any discharge around the gavage site. All patients had no problems with tube rotation or patency. The presence of a reaction around the gavage site was noted in four patients at the start of follow-up, with improvement observed thereafter. Granulation tissue was observed in one patient at the time of low-profile gastrostomy insertion. Conclusions. HEN patients with low-profile balloon gastrostomy placement generally have a low incidence of complications related to the presence of artificial access to the gastrointestinal tract.. The use of this type of tube in daily clinical practice should be considered on a case-by-case basis. It is advocated that this type of tube should be used more frequently in the HEN procedure.